Universal continuous-variable state orthogonalizer and qubit generator - Coehlho,AS; Costanzo,LS; Zavatta,A; Hughes,C; Kim,M; Bellini,M (Physical Review Letters, 2016)
We experimentally demonstrate a universal strategy for producing a quantum state that is orthogonalto an arbitrary, infinite-dimensional, pure input one, even if only a limited amount ofinformation about the latter is available. Arbitrary coherent superpositions of the two mutuallyorthogonal states are then produced by a simple change in the experimental parameters. We useinput coherent states of light to illustrate two variations of the method. However, we show that thescheme works equally well for arbitrary input fields and constitutes a universal procedure, whichmay thus prove a useful building block for quantum state engineering and quantum informationprocessing with continuous-variable qubits.